2008
DOI: 10.3748/wjg.14.5467
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from respiratory failure after decompression laparotomy for severe acute pancreatitis

Abstract: We present three cases of patients (at the age of 56 years, 49 years and 74 years respectively) with severe acute pancreatitis (SAP), complicated by intra-abdominal compartment syndrome (ACS) and respiratory insufficiency with limitations of mechanical ventilation. The respiratory situation of the patients was significantly improved after decompression laparotomy (DL) and lung protective ventilation was re-achieved. ACS was discussed followed by a short review of the literature. Our cases show that DL may help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Fortunately, animal and human studies have shown that abdominal decompressive laparotomy can reverse the pulmonary and abdominal detrimental effects of IAH Siebig et al, 2008). In the present study, with the relief of IAH after decompressive laparotomy, total lung volume and PaO 2 /FIO 2 improved while the diaphragmatic displacement and the non-aerated lung volume decreased (Although it improved, the PaO 2 /FIO 2 after decompressive laparotomy remained below the normal ranges).…”
Section: Discussionmentioning
confidence: 55%
“…Fortunately, animal and human studies have shown that abdominal decompressive laparotomy can reverse the pulmonary and abdominal detrimental effects of IAH Siebig et al, 2008). In the present study, with the relief of IAH after decompressive laparotomy, total lung volume and PaO 2 /FIO 2 improved while the diaphragmatic displacement and the non-aerated lung volume decreased (Although it improved, the PaO 2 /FIO 2 after decompressive laparotomy remained below the normal ranges).…”
Section: Discussionmentioning
confidence: 55%
“…Knowledge about surgical decompression for ACS in patients with SAP is limited and is mainly based on published case series with high mortality. 8,19,20 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, more and more studies are published promoting the decompression laparotomy for SAP patients developing ACS defi ned by IAP greater than 20 mmHg associated with new organ failure. This procedure can not only prevent a critical decrease of intestinal and renal perfusion, but may lead to an improvement of the respiratory situation (2,14).…”
Section: Management Of Iah In Patients With Sapmentioning
confidence: 99%